PENINGKATAN KETERAMPILAN BERBICARA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE ARTIKULSI PADA SISWA KELAS VI SD INPRES 3 TALISE - Kariani, Vitta (BAHASANTODEA, 2016)
Based on the explanation on the background of the research, so that, this research have a purpose to describe the application of speaking skills learning through articulation type of cooperative learning model at the sixth grade students of SD Inpres 3 Talise and to describe improving speaking skills through articulation type of cooperative learning at the sixth grade students of SD Inpres 3 talise. The kind of this research is a class action research. Design of this research reference at the Kurt lewin model which is adopted by Kemmis and Mc. Taggart (2012) that is include 4 steps : (a) planning, (b) implementation, (c) observation, and (d) reflection. Based on the meeting of the research, based on the evaluation speaking skills at the meeting of cycle I obtaining score at pronounciation aspects (69,71%), intonation aspect (69,71%), fluency aspect (60,57%), expression aspect (64%), and also respond compability aspect (63,43%). There are students who complete because achieved score of KKM (70) as many as 13 students or the percentage is 37,14%, whereas the students who not complete are 22 students or 62,86%. Getting the highest score is 80 whereas for the lowest score is 56. However at the cycle II the students who complete is achieved the score of KKM are 35 students (100%). based on the details the improvement speaking skills of the students can be seen at the result of five aspects evaluation speaking skills, those are pronounciation aspect (90,28%), intonation aspect (88,57%), fluency aspect (82,28%), expression aspect (82,86%), and respond compability aspect (87,43%). Average the achievement of those aspects (86,28%). There is the gettting a highest score is 96 whereas a lowest score is 72.